Utopian Conservation: Scientific Humanism, Evolution, and Island Imaginaries on the Galápagos Islands. (November 2020) - Bocci, Paolo
In 1959, the Charles Darwin Station and the Galápagos National Park were established, formally inaugurating conservation on the archipelago. In the same year, a utopian colony from the United States arrived. Whereas scholars have dismissed the latter and focused on the former, this essay unveils the science-inspired utopianism common to both enterprises. Investing science with the exclusive role of producing all knowledge and steering politics, leaders of the two initiatives aspired not only to protect nature but also to forge a new humanity. Describing how such ambitions burst along lines of race, class, and nationality, I argue that these enterprises consolidated the current understanding of the Galápagos as "pristine": a site fit for research and tourism but unhospitable to (other) people. Drawing on archival and historical documents, this essay aims to reinvigorate two conversations: one between science and technology studies (STS) and conservation, and the other between STS and utopian studies. If recent attempts at bridging the divide between science and imagination have emphasized how powerful actors shape human society, this essay considers the long-lasting effects of scientific imaginaries on a politics of nature.